Whole-body and segmental muscle volume are associated with ball velocity in high school baseball pitchers - Yamada Y; Yamashita D; Yamamoto S; Matsui T; Seo K; Azuma Y; Kida Y; Morihara T; Kimura M (Dove Medical Press, 2013)
Yosuke Yamada,1,2 Daichi Yamashita,2,3 Shinji Yamamoto,2,3 Tomoyuki Matsui,4 Kazuya Seo,4 Yoshikazu Azuma,4 Yoshikazu Kida,5 Toru Morihara,5 Misaka Kimura1 1Laboratory of Sports and Health Science, Kyoto Prefectural University of Medicine, Kyoto, Japan; 2Research Fellow, Japan Society for the Promotion of Science, Tokyo, Japan; 3Graduate School of Human and Environmental Studies, Kyoto University, Kyoto, Japan; 4Department of Rehabilitation, Graduate School of Medical Science, Kyoto, Prefectural University of Medicine, Kyoto, Japan; 5Department of Orthopedics, Graduate School of Medical Science, Kyoto Prefectural University of Medicine, Kyoto, Japan Abstract: The aim of the study was to examine the relationship between pitching ball velocity and segmental (trunk, upper arm, forearm, upper leg, and lower leg) and whole-body muscle volume (MV) in high school baseball pitchers. Forty-seven male high school pitchers (40 right-handers and seven left-handers; age, 16.2 ± 0.7 years; stature, 173.6 ± 4.9 cm; mass, 65.0 ± 6.8 kg, years of baseball experience, 7.5 ± 1.8 years; maximum pitching ball velocity, 119.0 ± 9.0 km/hour) participated in the study. Segmental and whole-body MV were measured using segmental bioelectrical impedance analysis. Maximum ball velocity was measured with a sports radar gun. The MV of the dominant arm was significantly larger than the MV of the non-dominant arm (P < 0.001). There was no difference in MV between the dominant and non-dominant legs. Whole-body MV was significantly correlated with ball velocity (r = 0.412, P < 0.01). Trunk MV was not correlated with ball velocity, but the MV for both lower legs, and the dominant upper leg, upper arm, and forearm were significantly correlated with ball velocity (P < 0.05). The results were not affected by age or years of baseball experience. Whole-body and segmental MV are associated with ball velocity in high school baseball pitchers. However, the contribution of the muscle mass on pitching ball velocity is limited, thus other fundamental factors (ie, pitching skill) are also important. Keywords: pitching, ball velocity, muscle volume, body composition, trunk, upper and lower extremities